The role of platelet MyD88 in host response during gram‐negative sepsis - Stoppelaar, S. F.; Claushuis, T. A. M.; Jansen, M. P. B.; Hou, B.; Roelofs, J. J. T. H.; Veer, C.; Poll, T. (Journal of thrombosis and haemostasis, 2015)
Summary Background Beside their role in hemostasis, platelets serve as sentinel cells in host defense during infection. In sepsis, platelets have been implicated in both beneficial (antibacterial) and detrimental responses (thrombosis and organ damage). Toll‐like receptors and their common adaptor, myeloid differentiation factor 88 (MyD88), are essential for pathogen recognition and protective immunity. Platelets express functional Toll‐like receptors and MyD88, which participate in platelet responsiveness to bacterial agonists. Objective Considering the pivotal involvement of platelets and MyD88 in the host response to bacteria, we studied the role of platelet MyD88 in gram‐negative sepsis using intravenous and airway infections with the common human sepsis pathogen Klebsiella pneumoniae. Methods Platelet‐specific Myd88−/− mice were generated by crossing mice with a conditional Myd88 flox allele with mice expressing Cre recombinase controlled by the platelet factor 4 promoter. In a reverse approach, full Myd88−/− mice were transfused with wild‐type platelets. Results In both settings, platelet MyD88 did not impact on bacterial growth or dissemination. In addition, platelet MyD88 did not influence hallmark sepsis responses such as thrombocytopenia, coagulation or endothelial activation, or distant organ injury. Platelet MyD88 played no role in lung pathology during pneumonia‐derived sepsis. Conclusion Despite known literature, platelet MyD88‐dependent TLR signaling does not contribute to the host response during gram‐negative sepsis.